THE SIGNIFICANCE OF FOCUSING ON STATE TERRORISM: A CRITICAL ANALYSIS - Rakhshanda Iqbal (International Journal of Contemporary Issues in Social Sciences, 2024)
State terrorism is as prevalent as terrorism committed by non-state actors. However, excessive attention has been given to the study of non-state terrorism whereas state terrorism which is far serious an issue remains largely overlooked and under researched. The silence that is maintained on terrorism committed by states is alarming indeed. There is a genuine need to break this silence. It is a serious mistake to equate terrorism with non-state actors only. It is equally wrong to consider terrorism in terms that it is only committed by non-Western states against the Western states. This study has attempted to highlight the significance of focusing on state terrorism and recognizing it as abhorrent an activity as terrorism by non-state actors is considered. Various debates on the subject in terrorism and Critical Terrorism Studies have been discussed at length to seek clarity regarding the nature of the issue.